Conjugated Porous Polymers Based on BODIPY and BOPHY Dyes in Hybrid Heterojunctions for Artificial Photosynthesis (Adv. Funct. Mater. 51/2021). (16th December 2021) - Collado, Laura; Naranjo, Teresa; Gomez‐Mendoza, Miguel; López‐Calixto, Carmen G.; Oropeza, Freddy E.; Liras, Marta; Marugán, Javier; de la Peña O'Shea, Víctor A.
Abstract : Artificial Photosynthesis In article number 2105384, Laura Collado, Marta Liras, Javier Marugán, Víctor A. de la Peña O'Shea, and co‐workers investigate hybrid heterostructures containing highly tuneable and photostable conjugated porous polymers (CPPs) coupled to inorganic semiconductors for solar fuel production via H2 evolution and CO2 photoreduction under UV/visible illumination. Photophysical studies reveal the potential of these hybrids to facilitate charge separation and transfer, considerably improving the photocatalytic activities for artificial photosynthesis or other light‐mediated energy solutions.